Anticoagulation for rheumatic mitral stenosis, INVICTUS in perspective. (22nd March 2023) - Verma, Raj; Latter, David A.
Abstract : Purpose of review: Rheumatic mitral stenosis (MS) while declining in high- and middle-income countries, continues to be a major cause of death and disability in low-income countries. Although the nonvitamin-K antagonist oral anticoagulants (NOACs) have essentially supplanted vitamin K antagonists (VKA) in patients with nonvalvular atrial fibrillation (AF), their efficacy for stroke prevention in patients with rheumatic MS and AF has not been widely studied until recently. The purpose of this review is to provide a succinct synopsis of the current anticoagulation recommendations for patients with native and prosthetic heart valve disease, with a specific focus on patients with rheumatic MS. Recent findings: The INVICTUS trial was the first large randomized evaluation of a NOAC vs. VKA in approximately 4600 patients with moderate to severe rheumatic MS and AF. The primary outcome of stroke, systemic embolization, myocardial infarction, vascular and all-cause death, VKA treated patients exhibited lower event rates (including mortality) compared to rivaroxaban. We discuss and contextualize these findings as they relate to the broader use of anticoagulants in patients with valvular heart disease, with and without concomitant AF. Summary: VKA remains the standard of care for patients with moderate to severe rheumatic MS who have concomitant AF. Rates of stroke in anticoagulated patients with rheumatic MS and AF are lower than what is traditionally held, while nonstroke related deaths remain the most common mechanism of mortality.